Visual Outcomes, Quality of Vision, and Quality of Life of Diffractive Multifocal Intraocular Lens Implantation after Myopic Laser In Situ Keratomileusis: A Prospective, Observational Case Series - John S. M. Chang; Jack C. M. Ng; Vincent K. C. Chan; Antony K. P. Law (Journal of Ophthalmology)
Purpose. To report visual performance and quality of life after implantation of a bifocal diffractive multifocal intraocular lens (MIOL) in postmyopic laser in situ keratomileusis (LASIK) patients. Methods. Prospective, observational case series. Patients with prior myopic LASIK who had implantation of Tecnis ZMA00/ZMB00 MIOL (Abbott Medical Optics) at Hong Kong Sanatorium and Hospital were included. Postoperative examinations included monocular and binocular distance, intermediate and near visual acuity (VA), and contrast sensitivity; visual symptoms (0–5); satisfaction (1–5); spectacle independence rate; and quality of life. Results. Twenty-three patients (27 eyes) were included. No intraoperative complications developed. Mean monocular uncorrected VA at distance, intermediate, and near were 0.13±0.15 (standard deviation), 0.22±0.15, and 0.16±0.15, respectively. Corresponding mean values for binocular uncorrected VA were 0.00±0.10, 0.08±0.13, and 0.13±0.10, respectively. No eyes lost >1 line of corrected distance VA. Contrast sensitivity at different spatial frequencies between operated and unoperated eyes did not differ significantly (all P>0.05). Mean score for halos, night glare, starbursts, and satisfaction were 1.46±1.62, 1.85±1.69, 0.78±1.31, and 3.50±1.02, respectively. Eighteen patients (78%) reported complete spectacle independence. Mean composite score of the quality-of-life questionnaire was 90.31±8.50 out of 100. Conclusions. Implantation of the MIOL after myopic LASIK was safe and achieved good visual performance.